Development of Quality Function Deployment Tool for Improved Customer Service in Cosmetics Manufacturing Company (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
Quality Function Deployment (QFD) is a systematic process used to integrate customer requirements into every aspect of the production and development process. This paper examines the application of QFD in manufacturing companies, highlighting its benefits, challenges, and practical implementation strategies, using a case analysis of EBI cosmetics manufacturing firm that successfully utilized QFD to improve product quality and customer satisfaction. The study aims to develop a quality function deployment tool for improved customer service in a cosmetics manufacturing company. In line with the study objectives, a unique software application named “Cosmeticsqfd”, which is designed to receive feedback from customers of EBI Nigeria Limited was developed and used to analyze consumer responses to a set of structured survey questions in real-time, using the QFD approach which was derived from the house of quality (HOQ) matrix. The software encoding was done using JavaScript programming language, the framework for the software was developed using React Native, while Firebase Firestore, was used to carry out data synchronization of consumer responses in real-time. The results obtained from the analysis, led to a rejection of the Null hypothesis and it revealed "price" to be the main influencing factor for customer purchase, as well as consumer satisfaction. A reliability test on the survey questions and client responses, revealed a Spearman’s correlation of 0.631 and this also validated the result, as it implies the existence of a significant relationship between the factor affecting customer purchase decision, as well as their level of satisfaction. In terms of long term benefits, the developed Cosmeticsqfd software is capable of identifying technical areas of improvement in a business and is therefore recommended for use in any enterprise where quality performance is required.
Keywords: Quality function deployment, House of Quality, Quality, Quality Assurance, Technical requirement